Job Stress and Safety Climate in Cancer Treatment Centers: Upgraded Model for Dimensions - yari, saeed; shahsavari, saeed; Nourmohammadi, Mohammad; khosravizadeh, omid; Fallah Asadi, Ayda (Asian Pacific Journal of Environment and Cancer, 2018)
Background: Stress has always been with human despite all the progress in science and technology. Stressful conditions reduce concentration and lead to the lack of focus. This can increase human errors and bring about catastrophe. The aim of this study is to present a model to increase safety climate by controlling job stress among the personnel of Iran’s medical centers. Methods: In this study, 680 personnel of Iran’s hospitals were chosen in random. Demographic, job stress (35 questions) and safety climate (37 questions) questionnaires were filled. The data were inserted in SPSS 20 software. Descriptive statistics method and Pearson’s correlation coefficient were used to describe the data and evaluate the relation between the variables, respectively. Results: The scores of safety climate and job stress were 3.40 and 3.21, respectively which imply that they are suitable. The overall fitness of the model was acceptable. In this model, χ2 = 6366.17, df= 2452, χ2/df = 2.596, RMSEA = 0.054 (90% CI = 0.000–0.084), NFI = 0.901, GFI=0.913, and CFI=0.856. In the regression analysis, there were positive significant relationships between job stress and safety climate, job stress and any of its components, and safety climate and any of the components. Conclusion: Job stress is directly related to safety climate. Since in this study job stress was in a suitable level, it influenced the safety climate. If job stress is high, then it can affect safety climate in a negative way. We suggest that further studies be done regarding this subject.